Correlation of feline immunodeficiency virus status and the severity of feline chronic gingivostomatitis - Reginaldo Pereira de Sousa Filho; Keytyanne de Oliveira Sampaio; Didier Quevedo Cagnini; Assis Rubens Montenegro; Mariana Araújo Rocha; Janaina Serra Azul Monteiro Evangelista; Marina Gabriela Monteiro Carvalho Mori da Cunha (Brazilian Journal of Veterinary Research and Animal Science, 2018)
Feline chronic gingivostomatitis (FCGS) is a challenge for the veterinary practitioner since its etiology and treatments are still undefined. The present paper investigated the role of the feline immunodeficiency virus (FIV) in the severity of the FCGS. Oral mucosal biopsies obtained from 19 cats with FCGS were divided into two groups according to their FIV serology status. Later, the clinical lesion score was correlated with the histopathological grade of FCGS lesions and the degree of immunostaining in both groups. Most of the animals had significant histological changes; however, no correlation with FIV immunostaining intensity was observed. It was concluded that the presence of FIV infection or the animal’s seropositivity status does not seem to interfere with the severity of clinical signs nor the degree of histopathological changes when compared to the seronegative group.